Peningkatan Sumberdaya Manusia Dalam Menggapai Bisnis Bersekala Global Di Indonesia - Dita Rachmawati; Anudiyan Amir Mas’ud (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
In this research, the researcher aims to gain a true understanding of international business in Indonesia, and by using this method, he can reveal comprehensively how the incidental export process works: active export; license sales; franchising; overseas marketing; overseas production and marketing. International business is a business whose activities cross national borders. This definition includes not only international trade and overseas manufacturing but also developing service industries in areas such as transportation, tourism, banking, advertising, construction, retail trade, wholesale trade, and mass communications. International marketing is different from international business. International trade is a transaction between countries that is usually carried out in traditional ways, namely by exporting and importing. With these export and import transactions, a balance of trade between countries arises (balance of tread), while international marketing is a situation where a company can be involved in a business transaction with another country, another company, or the general public abroad. These international business transactions are generally an effort to market production results abroad.